2013
DOI: 10.1002/asi.22984
|View full text |Cite
|
Sign up to set email alerts
|

A knowledge‐based approach for polarity classification in Twitter

Abstract: Until now, most of the methods published for polarity classification in Twitter have used a supervised approach. The differences between them are only the features selected and the method used for weighting them. In this article, we present an unsupervised method for polarity classification in Twitter. The method is based on the expansion of the concepts expressed in the tweets through the application of PageRank to WordNet. In addition, we integrate SentiWordNet to compute the final value of polarity. The syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 33 publications
0
11
1
1
Order By: Relevance
“…Thereafter, compare the calculated score with the minimum subjective score to identify and remove the objective sentence from review, as shown in Lines 9 to 11. The prior studies (Montejo‐Ráez, Martínez‐Cámara, Martín‐Valdivia, & Ureña‐López, ; Paltoglou, Gobron, Skowron, Thelwall, & Thalmann, ) utilized subjective score from 0.4 to 1.0 to determine the subjectivity of sentence; therefore, we take 0.6 as a minimum subjective score for subjective classification. At the end, the remaining subjective sentences of each review are joined by using a dot (.)…”
Section: Proposed Modelmentioning
confidence: 99%
“…Thereafter, compare the calculated score with the minimum subjective score to identify and remove the objective sentence from review, as shown in Lines 9 to 11. The prior studies (Montejo‐Ráez, Martínez‐Cámara, Martín‐Valdivia, & Ureña‐López, ; Paltoglou, Gobron, Skowron, Thelwall, & Thalmann, ) utilized subjective score from 0.4 to 1.0 to determine the subjectivity of sentence; therefore, we take 0.6 as a minimum subjective score for subjective classification. At the end, the remaining subjective sentences of each review are joined by using a dot (.)…”
Section: Proposed Modelmentioning
confidence: 99%
“…As large efforts are put by the researchers in the field of sentiment analysis during the last two decades, it results in several methods and models being proposed. These models based on two approaches: supervised learning [3] [8] and lexicon-based approach [9] [10] [11]. Lexicon is a collection of the predefined word where a polarity score is associated with each word [12].…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are numerous publications about this topic and its applications; see (Liu, 2012;Feldman, 2013) for reviews which summarizes the general sentiment analysis problems and methods, and (Ravi and Ravi, 2015) for a more recent survey which also deals with cross-lingual sentiment analysis. Because tweets are forming a specific text genre there are many papers about the difficulties and method of SA in Twitter (Martínez-Cámara et al, 2012;Montejo-Ráez et al, 2014). In our paper, we comparatively evaluated task-specific techniques and their performance on various text genres and languages.…”
Section: Related Workmentioning
confidence: 99%